2020
DOI: 10.1021/acsmaterialslett.9b00539
|View full text |Cite
|
Sign up to set email alerts
|

Triggerable Ion Release in Polymerized Ionic Liquids Containing Thermally Labile Diels–Alder Linkages

Abstract: Controlling the mobile ion content of ioncontaining polymers is critical for advanced organic electronic applications. Here, we report a chemical strategy for achieving "on-demand" release of ions in polymeric materials by incorporating thermally labile Diels−Alder linkages into polymerized ionic liquids. Electrical characterization demonstrates a clear increase in mobile ion content at the retro-Diels−Alder temperature, which is retained after the material is returned to room temperature. This work demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The results of the chemically locked, gateless, graphene p-n junction serve as proof-of-concept that alternate triggers can be used to semi-permanently dope 2D devices for room temperature operation. In fact, we have also recently shown that incorporation of thermally-labile linkers into polymerizable ionic liquids allows ions to be released after the materials are polymerized, which we anticipate will enable DPILs that can be locked and then unlocked with a second trigger [54]. This type of locking and unlocking-especially if it can be field-controlled-could prove useful for polymorphic circuits.…”
Section: P-n Junction Formation Using Dpilmentioning
confidence: 92%
See 2 more Smart Citations
“…The results of the chemically locked, gateless, graphene p-n junction serve as proof-of-concept that alternate triggers can be used to semi-permanently dope 2D devices for room temperature operation. In fact, we have also recently shown that incorporation of thermally-labile linkers into polymerizable ionic liquids allows ions to be released after the materials are polymerized, which we anticipate will enable DPILs that can be locked and then unlocked with a second trigger [54]. This type of locking and unlocking-especially if it can be field-controlled-could prove useful for polymorphic circuits.…”
Section: P-n Junction Formation Using Dpilmentioning
confidence: 92%
“…were synthesized according to reference [52][53][54]. One mg of the initiator, azobisisobutyronitrile (AIBN), was dissolved in 100 µL unpolymerized DPIL monomer, and then drop-cast in the glovebox (25 µL over 1 cm 2 ) with thickness estimated to bẽ 200 µm according to the cast volume.…”
Section: Electrolyte Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chain growth polymerization (i) requires an IL monomer with an unsaturated or cyclic chemical structure that can be activated during the polymerization step ( Figure 5 ). Such a bond is often synthetically introduced into IL monomers (ILM) through the incorporation of methacrylic and methacrylamide [ 112 , 148 , 149 , 150 ], vinyl and styrene [ 116 , 151 , 152 , 153 , 154 , 155 ], or norbornene [ 156 , 157 , 158 ] or epoxy moieties. The sheer number of these reports demonstrates the applicability of this approach and underlines its advantages.…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 99%
“…Initial reports of PILs synthesis emerged at the beginning of the 2000s and mostly employed conventional free radical polymerization (FRP) [ 159 , 160 ]. While allowing a straightforward preparation of PILs from monomers, it builds from pre-existing double bonds in methacrylate [ 149 , 161 ], vinyl- [ 155 , 161 , 162 , 163 , 164 ], and styrene [ 154 ] building blocks. In this case, the synthetic approach would include at least three steps to prepare a PIL with a halide anion: (i) Halide incorporation; (ii) quaternization; (iii) polymerization in the presence of an initiator (i.e., AIBN).…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 99%